Bistatic Transfer Function for a Planar Distribution of Stationary Scatterers: Analytical Results - Cabrera, Octavio (2015)
We present exact and approximate analytical results for signal transmission through a planar distribution of stationary scatterers in a bistatic configuration. The transfer function of this transmission channel is computed by assuming a continuous cross-section density. This approach makes it possible to obtain explicit mathematical expressions for a wide variety of scatterer distributions. The inverse problem, where the scatterer distribution is inferred from the transfer function, is also considered. Analytical results are compared with numerical simulations for randomly distributed point scatterers, using real-life FM signals. Transfer functions for these stylized scatterer distributions may provide a base for more realistic mathematical models of the environment.